1998
DOI: 10.1097/00042560-199809010-00014
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Progression of HIV Infection in a Greek Hemophilia Cohort Followed for Up to 16 Years After Seroconversion

Abstract: Our objectives are to describe the progression of HIV disease and to assess the influence of hemophilia-related variables, age at infection, and antibodies to cytomegalovirus infection (anti-CMV) in a Greek cohort of 158 HIV-1-positive hemophilic men, who received prospective follow-up for up to 16 years after infection. A total of 79 patients had died, representing a cumulative progression rate of 72.4% (95% confidence interval [CI], 56.6-83.3). A significant proportion of the mortality (30%) resulted from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
2
15
2
Order By: Relevance
“…The older age in an HIV-infected individual has been found in several studies to be correlated with rapid disease progression. 31,32 Our analysis also showed that older age was associated with shorter time to the AIDS progression and survival. Survival was shorter among men than women but did not differ in the time to AIDS progression.…”
Section: Discussionsupporting
confidence: 56%
“…The older age in an HIV-infected individual has been found in several studies to be correlated with rapid disease progression. 31,32 Our analysis also showed that older age was associated with shorter time to the AIDS progression and survival. Survival was shorter among men than women but did not differ in the time to AIDS progression.…”
Section: Discussionsupporting
confidence: 56%
“…Due to the late entry of infected individuals into HIV diagnosis programs, the authors hypothesize that the very high number of AIDS deaths and the very short survival time for individuals after HIV infection in Nigeria and in most of sub-Saharan Africa could be attributed to the fact that the majority of these patients access health care late during the course of natural HIV infection. The median time from seroconversion to AIDS in industrialized countries is far longer than is suggested in this study and other studies from Africa [32,33,34,35], which in the past has been taken as evidence of rapid progression of the disease in Africa, as a high proportion of Africans infected with HIV-1 die sooner after HIV diagnosis than their counterparts in industrialized countries. This, however, does not seem to be the case.…”
Section: Discussioncontrasting
confidence: 51%
“…To illustrate the issue, data on CD4 cell counts from the Greek Haemophilia Cohort Study (GHCS) will be used. A total of 158 HIV-infected hemophiliac men with known seroconversion (SC) dates were enrolled in the GHCS and followed prospectively [31]. Clinical information and data on laboratory parameters were to be collected every 6 months.…”
Section: Missing Data In Hiv-1 Studies: the Greek Haemophilia Cohort mentioning
confidence: 99%